Prevalence of Foot and Mouth Disease and Evaluation of Effectiveness of Vaccination in Malaysian Cattle. - Hamad Hasaballa, Aamir Abbo (2010)
Foot and Mouth Disease (FMD) is an important viral disease of cloven-hoofed animals and is caused by the Foot and Mouth disease Virus (FMDV) which is a species of the Aphthovirus genus in the Picornaviridae family. The virus is an important cause of FMD infection in the temperate, tropical and non-tropical regions. In Malaysia, a tropical country, the occurrence of FMD infection in cattle is not uncommon. Strategic vaccination of livestock in the states close to Thailand border has in the past- successfully controlled the disease. However, the situation has changes since then and FMD is now widespread throughout the peninsular. Thus, an epidemiological investigation to assess the vaccination effectiveness, the level of immunity conferred in vaccinated cattle and the common vaccine handling and practices in Peninsular Malaysia is essential for an effective control and eradication programme. The present study was carried out to describe the FMD outbreak in Peninsular Malaysia between 1996-2007, to determine the coverage rate for FMD vaccination between 1996-2007, to determine the levels of the antibodies (Ab) response pre and post-vaccination, to examine the vaccination procedures and to identify the potential risk factors associated with the vaccine failure. Available records and data in the Department of Veterinary Services (DVS) headquarters in Putrajaya, FMD Regional Laboratory in Kota Bahru, Kelantan and OIE website on SEAFMD reports (www.oir.int) were examined and analysed to describe the FMD outbreaks in Peninsular Malaysia and determine the coverage rate for FMD vaccination between 1996 and 2007. The study found the vaccination coverage rate for the 12-year period was 56.5%. The overall prevalence rate of FMD in cattle within the period of 12 years was 11.1% with a case-fatality rate of 0.62%. The highest number of FMD outbreaks (83) occurred in 1997, while the lowest number of FMD outbreaks (1) was in 2000. The highest number of FMD cases was in 2004. The monthly outbreak pattern of FMD during this 12-year period showed a sharp increase in the number of outbreaks during the Northeast Monsoon season in which the outbreaks number reached a peak in the month of December. Among the cases, (83.4%) were due to serotype O FMDV, followed by type A (11.9%) and type Asia 1 (4.7%). A prospective cohort study was carried out in one Government large scale beef farm (Farm A) and one small-scale beef farm (Farm B) in Perlis state which represented FMD less-endemic area and one Government large scale breeding farm (Farm C) in Kelantan state which is FMD endemic area. The aim of this part of the study was to measure the antibody levels pre and post-vaccination using the commonly used FMD vaccine within Peninsular Malaysia. Blood sampling on each farm was performed in day 0 (<6 or day of vaccination), day 7-14, day 28-100 and day >100 for a period of nine methods to cover the vaccine lifespan. A questionnaire on individual animals, disease occurrence and farm management was developed and the data were collected at the time of blood sampling. Solid Phase Blocking (SPB) ELISA Type O was performed to detect antibodies against structural proteins of type O FMDV in cattle and Non Structural Protein (NSP) ELISA was performed to differentiate whether the antibody formation was the result of vaccine or due to natural infection. The baseline of the SPB ELISA type O percentage inhibition (PI) of the animals indicated that 84.6% were strongly positive (PI >90) and only 7.4% were negative. The finding from NSP ELISA indicated that a low propotion of animals had been exposed to a natural infection. Thus indicates that the virus was circulating in the cattle population during the period of sampling, even though they were not showing any clinical FMD signs. The Ab response from cattle in Kelantan appears to be more rapid and longer lasting compared to the Ab response of cattle in Perlis. A total of 13 cattle were antibody negative at the beginning of the study later showed the desired increase in the antibody levels within the documented ideal time. A cross-sectional survey was conducted by developing and mailing a questionnaire on vaccine storage and handling to district veterinary offices around Peninsular Malaysia. This part of the study examined the vaccination procedures and identified the potential risk factors associated with vaccine failure. It was found that a few of the district respondents store vaccines in the freezer door shelves which may allow the vaccines to freeze and affect the quality of the vaccine. Most of the respondents applied the vaccine intramuscularly instead of the recommended subcutaneous route and more than half of the districts used expired vaccine in an emergency vaccination. In conclusion, the vaccine coverage rate between 1996 and 2007 period in Peninsular Malaysia was low and not adequate to confer a high level of herd immunity. The vaccination is a useful tool to control the FMDV as it increases the antibody level effectively however, improvement of staff knowledge and quality assurance practices related to vaccine storage and handling in district veterinary offices in Peninsular Malaysia is highly required to prevent vaccine failure.